Community Aspiration Services from Perspectives Transparency, Accountability, and Equal Rights: Study on Representatives of West Java People - Purwadewi Sundari, Ineu; Mariana, Dede; ., Muradi; Setiabudi Sumadinata, Widya (International Journal of Engineering and Technology, 2018)
This study discusses the performance of local legislative councils in the distribution of community efforts in West Java, Indonesia. The performance of Board members relates to transparency, accountability and equality. Using descriptive-qualitative methods, the review of this study found that the members of the Provincial Council always performed their duties as elected representatives to serve the community. For example, members of the Provincial Council absorb and collect voters' aspirations through regular working visits; Adapting and pursuing aspirations and grievances and providing a moral and political electoral constituency. All of that they do with transparent, accountable, and consider the equality of rights. Based on public opinion, the quality of service to the public provided by West Java Parliament is still fluctuating, meaning it is still up and down. However, it indicates the openness in its processes.Â Â